The Architecture of Paradiplomacy Regime in Indonesia: A Content Analysis - Surwandono, Surwandono; Maksum, Ali (UI Scholars Hub, 2020)
Paradiplomacy as a policy and practice of foreign policy by local governments have been carried out by the Indonesian government. But the practice of paradiplomacy shows a gap between local governments, as there are local governments that are so intensive but, on the other hand, some are passive. This article explains the architecture of paradiplomacy in the constitutional dimension through tracking the message structure in a number of regulations with content analysis methods. The advance of content analysis in the constitutional dimension will be able to provide comprehensive analysis on the architecture of Indonesia's paradiplomacy and its implications for achieving national interests. This article finds that Indonesia's paradiplomacy architecture is still very administrative, procedural, and technical, which results in inability to accelerate paradiplomacy by local governments in Indonesia to progressively attain local and national interests.